Court Affirms Adolescents’ Right to Gender Recognition (Human Rights Watch, 2026)
Ecuador’s Constitutional Court’s ruling that people under 18 cannot automatically be refused a request to modify their gender on identity documents is an important victory for the rights of transgender youth.
Ecuador